Imóveis não utilizados e a aplicação do Parcelamento, Edificação ou Utilização Compulsórios (PEUC) em São José do Rio Preto-SP - Silva, Luis Filipe Costa da (Universidade Federal de São Carlos, 2025)
Contextualization: Identifying vacant buildings that do not fulfill their social functions in urban areas is essential for directing urban management strategies focused on combating property vacancy. Compulsory, Subdivision, Building and Utilization of land (CSBU) is the fundamental urban policy instrument focused on combating this phenomenon, as provided for in the Federal Constitution and the City Statute. Justification: The 2022 Demographic Census recorded a 150% increase in the number of vacant homes in the Municipality since the 2010 Census. 13% of homes in the Municipality are vacant. Purpose: This research proposes to identify vacant buildings, subject to application of the Compulsory, Subdivision, Building and Utilization of land (CSBU) instrument in São José do Rio Preto-SP, in order to encourage the fulfillment of the social function of vacant urban property. Materials and Method: The Methodology for Identification of Potentially Vacant Properties (MIPVP) was adopted as a parameter to identify properties on a neighborhood scale, through using of seven variables that formed the Multicriteria Vacancy Index (MVI), in very high, high and low to medium vacancy, which supported field survey and identification of properties subject to CSBU application. Results and discussions: The spatialization of the parameters adopted in the construction of the MVI, prepared based on the survey, analysis and systematization of data, made it possible identify 57,65% of the neighborhoods in the municipality to be classified as low to medium property vacancy, 30,75% as highly property vacancy and 11,60% as very highly property vacancy. The Central Macroregion had the largest number of neighborhoods in the very highly property vacancy category, with 33 neighborhoods, corresponding to 5,55% of the total neighborhoods in the municipality. The field survey identified, in the Central Macroregion, that 36% of the neighborhoods investigated have 1 to 6,7% of their buildings considered vacants, 40% have 6,7 to 12,3% of their buildings vacants, and 24% have 12,3 to 18% of their buildings vacants. Regarding vacancy, 26% of neighborhoods have 0 to 33% of their buildings vacant for two years or more, 30% of neighborhoods have 33 to 67% of their buildings vacant for two years or more, and 44% of neighborhoods have 67 to 100% of their buildings vacant for two years or more. Regarding the applicability of CSBU, 08 neighborhoods were classified as low priority or third stage of application, 09 neighborhoods as medium priority or second stage of application, and 13 neighborhoods as high priority or first stage of application of CSBU. Conclusions: It is concluded that the use of MIPVP in São José do Rio Preto has achieved significant advances in identifying vacant buildings since the construction of the MVI until the field survey and demarcation of neighborhoods with buildings eligible for the application of CSBU. Its also importante to note that the scale of the data is essential to ensure that vacant buildings effectively. The closer the scale of the data is to the property, the more effective the use of MIPMP will be for applying CSBU.
Vacant buildings and the application of Compulsory, Subdivision and Utilization of Land (CSBU) in São José do Rio Preto-SP
Keywords: Imóveis não utilizados; Parcelamento, Edificação ou Utilização Compulsórios (PEUC); Metodologia para Identificação de Imóveis Potencialmente Ociosos (MIIPO); São José do Rio Preto; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL